Institutional Support for Families Taising Children with Disabilities in the Context of Social Inclusion: Analysis of Children’s Day Centers - Gardziulevičienė, Laura (Jaunųjų mokslininkų darbai, 2021)
The article examines the availability of institutional support for families raising children with disabilities. The aim of the study is to identify opportunities for social inclusion of children with disabilities in the children’s day center. Families raising children with disabilities are unable to function fully in public life due to the lack of access to services. Access to services and assistance, for the most vulnerable groups, depends on the attitude of state social policy makers, financial resources, cooperation, public involvement and, ultimately, the family’s own readiness to participate in public life. The methods of analysis, synthesis, generalization and comparative analysis of scientific literature were used in the research.The research revealed that the mechanism of children’s day care centers operating in Lithuania does not correspond to the model of creating an inclusive environment. Therefore, political decisions are needed on the development of services and the development of social inclusion at both the state and municipal levels, taking into account the needs of families raising children with disabilities. The practical significance of the study is that the study is useful for improving the accessibility of social services for families with children with disabilities and developing the concept of social inclusion.
Keywords: social inclusion; children’s day center; children with disabilities; social services